Strategi Pertumbuhan Usaha Cafe Titik Nol - Sulfiani Sulfiani; Sumiati Sumiati; Haedar Akib; A.Octamaya Tenri Awaru (Universitas Hamzanwadi, 2022)
To develop a business or business to be successful, it depends on how to run the business according to the rules and pay attention to the changes that occur. Zero point cafe is a self-owned business, not a child of an entrepreneur or a branch of a medium or large business. Zero point cafe is managed by one of Hasanuddin University's undergraduate program students named Ajrullah Sumaji, this cafe is located on Jln Statistik, Tamalanrea Indah, Makassar City.This study aims to determine the business growth strategy and the factors that influence the Café Point Zero business. To achieve this goal, the researchers used data collection techniques through individual interviews. The data obtained from the research results are processed using qualitative descriptive data to find out what strategies are carried out or used by Point Zero Café in increasing its business growth and what factors influence the business growth strategy of Point Zero Café..The results showed that (1) the Point Zero café business growth strategy was carried out by making more use of social media as a tool to promote the cafe, fostering existing relationships with cafe employees to enliven or find regular cafe customers, providing the best service to all consumers, take advantage of technological developments in running a business. always trying to improve facilities to improve customer convenience, trying to maintain a consistent taste of the products sold. (2) the factors that influence the growth strategy of the Zero Point Café Business, namely internal factors and external factors. Internal factors include strengths and weaknesses. The strengths of Point Zero Café are the café's image, the strategic location of the café, the quality of the products offered, adequate advice and infrastructure, having regular customers, and perfecting innovative and creative products. Meanwhile, the weakness of this café is the lack of promotional activities, marketing network, and limited marketing personnel. External factors include opportunities and threats. Opportunities owned by the Cafe include (1) Hasanuddin University student growth rate (2) An increasing sales trend. While the threat for Point Zero Café is during the current covid 19 pandemic, of course this cafe is not operating properly.